Smart grid planning and implementation - Gellings, Clark W. (Fairmont Press, Inc., CRC Press, Taylor & Francis Group, 2015)
This book is intended for electric utility managers, directors, and power system planners, regulators, and policy makers interested in the steps needed to realize the value of a modern power delivery system. This book describes the elements needed in planning and implementing a 'Smart Grid' by outlining how the electricity delivery system can be modernized so it monitors, protects, and automatically optimizes the operation of its interconnected elements - from the central and distributed generator through the high-voltage network and distribution system, to energy storage installations and to end-use consumers and their thermostats, electric vehicles, appliances, and other household devices.
Keywords: Smart power grids.; elektronické knihy; electronic books